2022
DOI: 10.1039/d1ra08997h
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of the elimination of copper, cadmium, and methylene blue from water by adsorption on the citrus Sinensis peel and its activated carbon

Abstract: The accumulation of heavy metals and dyes in wastewater is a persistent environmental threat with serious hazards consequences affecting all living organisms. Citrus Sinensis peel and its activated carbon particles effectively remove Cu(ii), Cd(ii), and MB from water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…The Figure 7 , Figure 8 and Figure 9 show a typical measurement of organic dye absorbance vs. reaction time after exposure to a UV-Vis lamp with a longer wavelength of 670 nm. In methylene blue, the hetero-poly aromatic bond between the S and N atoms accounts for the high absorbance at 664 nm [ 42 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…The Figure 7 , Figure 8 and Figure 9 show a typical measurement of organic dye absorbance vs. reaction time after exposure to a UV-Vis lamp with a longer wavelength of 670 nm. In methylene blue, the hetero-poly aromatic bond between the S and N atoms accounts for the high absorbance at 664 nm [ 42 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
“… 14 − 16 Adsorption processes are easy to handle, simple in design, and very cost-effective. 15 Various types of locally available low-cost adsorbents and their activated carbon have been employed for the adsorption of lead ions from contaminated wastewater. 12 Over the last decade, activated carbon has been tremendously used because of its availability, physical and chemical stability, high surface area, adsorption capacity, and porous structure.…”
Section: Introductionmentioning
confidence: 99%
“…Heavy metals are often removed using a variety of techniques, including solvent extraction, electrolysis, coagulation, reverse osmosis, chemical precipitation, ion exchange, and membrane separation. , However, all these techniques are generally expensive and have many disadvantages such as high operational cost and energy requirements, incomplete removal, the use of chemicals, and the generation of toxic and waste byproducts. ,, Therefore, there is a pressing need to create methods for reducing waste and wastewater reclamation that are both affordable and environmentally benign. The most efficient and promising alternative greener technique gaining popularity for metal ion removal is adsorption. Adsorption processes are easy to handle, simple in design, and very cost-effective . Various types of locally available low-cost adsorbents and their activated carbon have been employed for the adsorption of lead ions from contaminated wastewater .…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, the Langmuir model was proposed based on the theory that all the sites of absorbent have an equal affinity toward the ions and the ions may form a monolayer coat on the surface of the absorbents, while the Freundlich model based on the equilibrium relationship between inhomogeneous surface and suggested an inhomogeneous system. 49,50 Combined with the fitting results, we can concluded that the adsorption of hexavalent chromium was a multi-molecular layer adsorption process and parts of the adsorbed Cr( vi ) ions were tightly bonded to the nZVI–BC surface and were not readily desorbable. 48…”
Section: Resultsmentioning
confidence: 73%